Metabolic Engineering Of Cupriavidus Necator For The Production Of Poly (3-Hydroxybutyrate-Co-3-Hydroxyhexanoate - Ab Ghani, Balqis (2017)
Polyhydroxyalkanoate (PHA) is a family of polyesters produced by bacteria that possesses physical properties for various industrial applications. In this study, PHA synthase (PhaC) gene isolated from Chromobacterium sp. USM2 (phaCCs USM2) was explored for its potential to synthesize polymer in Cupriavidus necator. A broad-host range plasmid pBBR1MCS-2 was modified to construct an expression plasmid pYEB-100, which was designed to facilitate cloning of PHA synthases in order to assess the performance of various PhaCs and the composition of PHA accumulated in a standard environment.